The Spatial and Temporal Repeatability of Genomic Responses to Natural Selection as Demonstrated in Stickleback Populations Experiencing Highly Dynamic Environments - Mary Kathleen Hickox; Ben A. Wasserman; Alan Garcia‐Elfring; Eric P. Palkovacs; Andrew P. Hendry; Rowan D. H. Barrett (Molecular Ecology, 2026)
The evolution of genotypic parallelism under shared environmental conditions provides strong evidence for the role of natural selection. However, analyses typically examine genomic signatures of selection long after the putative selection event and only assess the repeatability of responses across spatial population replicates. This impedes our ability to attribute a particular response to a given selection pressure and to distinguish non‐parallel responses caused by stochastic processes from those caused by local selection. As such, the consistency of natural selection over space and time is unknown, and the role of persistent local selection pressures is unclear. Here, we leveraged the natural bar‐built estuary system of Santa Cruz, California, to examine the repeatability of seasonal genomic change in threespine stickleback ( Gasterosteus aculeatus ) over space and time. By comparing allele‐frequency shifts that are shared across locations (spatial repeatability) with those that are shared across years within locations (temporal repeatability), we identified both spatially shared and local components of putative selection. We found that repeated seasonal outlier responses occurred more often than expected under a neutral null model. Although repeatability declined as the number of estuaries sharing an outlier increased, enrichment above neutral expectations increased with broader spatial sharing, particularly for outliers repeated across both years. While the precise outlier SNPs varied across years, estuary‐specific patterns of responses were broadly consistent, suggesting an important role for local conditions. Together, our findings show that temporal sampling can reveal components of putative selection that would be missed from spatial comparisons alone. More broadly, they highlight the importance of examining repeatability over both space and time to understand the parallel and non‐parallel components of adaptive genomic change.

Using Drone‐Derived Imagery to Describe Prey Sharing Behaviors in Two Piscivorous Resident Killer Whale Populations - Sharon W. C. Kay; Lance G. Barrett‐Lennard; Brittany C. Visona‐Kelly; Marie‐Ana Mikus; Michael N. Weiss; Darren P. Croft; Valeria Vergara; Holly Fearnbach; John W. Durban; Chris T. Darimont (Marine Mammal Science, 2026)
Cooperative foraging occurs across diverse taxa and facilitates prey acquisition and social learning, particularly when prey is shared among group members. In Resident killer whales ( Orcinus orca ater ), prey sharing is central to how individuals acquire salmonid prey, yet current research has relied primarily on boat‐based observations. Using 10 years of drone‐based imagery, we examined prey sharing behaviors in two populations, endangered Southern Resident killer whales (SRKWs) and threatened Northern Resident killer whales (NRKWs). Our goal was to evaluate the utility of drones for documenting prey sharing behaviors and conduct preliminary comparisons between NRKW and SRKWs. We detected 41 NRKW and 52 SRKW predation events, with prey sharing observed in 24 NRKW (59%) and 22 SRKW (42%) events. Drones effectively documented prey sharing at or near the surface, revealing subtle behaviors and allowing us to track the roles of individuals. Initial comparisons revealed that adult female NRKWs shared prey more frequently than adult female SRKWs and shared larger portions of prey. Although preliminary, our findings suggest differences in prey sharing between the populations, possibly reflecting social or ecological differences. Overall, drone‐based methods provide valuable insights into foraging behavior in free‐ranging cetaceans and offer a new approach to investigate cooperative behaviors.

Gestational exposure to organophosphate ester flame retardants and child growth in weight, height, and body mass index at age 2-10 years: the Environmental influences on Child Health Outcomes Program - Anne P. Starling; Xuan Li; Jennifer L. Ames; Emily S. Barrett; Theresa M. Bastain; Claudia Buss; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Monique M. Hedderson; Julie Herbstman; Kurunthachalam Kannan; et al. (Environmental Research, 2026)

Using herd frailty estimates from survival models in a mortality-based syndromic surveillance system - Jaden M. Carlson; T. Brendan Murphy; Luke O’Grady; Jonas Brock; Maria P. Guelbenzu-Gonzalo; David A. Graham; Guy McGrath; Jamie A. Tratalos; Rafael de Andrade Moral; Niamh Mimnagh; Niamh L. Field; John F. Mee; et al. (Preventive Veterinary Medicine, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Prenatal exposure to organophosphate ester flame retardants and child cognition: Findings from the environmental influences on child Health Outcomes cohort - Akhgar Ghassabian; Taylor Etzel; Jennifer L. Ames; Thomas G. O'Connor; Jessie P. Buckley; Sarvenaz Shahin; Julie B. Herbstman; Emily S. Barrett; Donghai Liang; Lisa A. Croen; Rebecca J. Schmidt; Lesliam Quirós-Alcalá; et al. (Environmental Pollution, 2026)

An examination of the interaction between the interoceptive and reinforcing properties of morphine: a self-administration study in male and female rats - Allyson K. Andrade; Briana Renda; Adiia P. Stone; Michael Sharivker; Jessica M. Karlovcec; Rita El Azali; Francesco Leri; Scott T. Barrett; Jennifer E. Murray (Psychopharmacology, 2026)

Psychosocial stressors as modifiers of the associations between well-studied and understudied chemicals and birth outcomes in the ECHO Cohort - Stephanie M. Eick; Patricia A. Brennan; Jessie P. Buckley; Donghai Liang; Xiuhong Li; Kayla L. Karvonen; Whitney Cowell; Yeyi Zhu; Emily S. Barrett; Alicia K. Peterson; Brennan H. Baker; Max Aung; et al. (Environmental Pollution, 2026)

Evaluating the use of rodents as in vitro, in vivo and ex vivo experimental models for the assessment of tyrosine kinase inhibitor-induced cardiotoxicity: a systematic review - Lucy Gill; Amy Chadwick; Annette P. Meeson; Richard Barrett-Jolley; Marie M. Phelan; Rachel A. Oldershaw (Archives of Toxicology, 2025)
Tyrosine kinase inhibitors (TKIs) are widely used in cancer therapy yet are strongly associated with acute and chronic cardiotoxicity in patients. There is a critical need to advance our understanding of the pathophysiology that underlies TKI-mediated cardiotoxicity, and central to this is the use of reproducible and relevant preclinical models, which are employed in the evaluation of TKIs across the drug discovery pipeline. We have conducted a systematic review of the literature to determine how rodent models are used in the measurement of TKI-induced cardiotoxicity, focusing on animal reports, physiological cardiac outputs, histopathology, and biomarkers. A PRISMA-compliant systematic review was conducted using PubMed, Scopus, and Web of Science to identify studies reporting on TKI-induced cardiotoxicity in rodents. Only controlled in vivo, primary in vitro, and ex vivo studies using rats, mice, hamsters or guinea pigs were included. Data were extracted on species, strain, sex, age, experimental design, and cardiac outcomes with risk of bias analyses performed using the SYRCLE and SciRAP tools. Among 92 studies, sunitinib, imatinib, and sorafenib were the most frequently examined TKIs, with cardiotoxicity exhibited as altered cardiac functional parameters, fibrotic changes, arrhythmias, and elevated cardiac biomarkers. Rats (51 studies) and mice (46 studies) were predominantly used to study the effects of TKIs, whilst guinea pigs were underrepresented, limiting insights into electrophysiological changes that are associated with cardiotoxicity. Most studies used male rodents, and only two studies assessed age-related effects. Comparison between species strains was rarely conducted, despite evidence of this being a contributing factor to pre-disposition to cardiotoxicity. Rodent models were shown to replicate TKI-induced cardiotoxic effects observed in humans, but risk of bias analyses revealed limited evidence for study randomisation, inconsistent blinding, lack of sex-balanced studies, and poor strain diversity. Poor methodological quality and reporting across studies compromised reproducibility and interpretation of clinical relevance. Our study highlights the need for implementation of standardised protocols, strain, sex and age-stratified analyses to better support preclinical-to-clinical translation, as well as improve the safety of TKIs for patients and ensure more ethical use of animals in research.

Shifts in suitability of pinyon-juniper communities: A climate adaptation framework for range-wide management of arid woodland resources - Adam Noel; Daniel R. Schlaepfer; Ian P. Barrett; Michael C. Duniway; Jodi Norris; Chris T. Domschke; Brad J. Butterfield; Megan C. Swan; Kim Hartwig; Michele R. Crist; John B. Bradford (Forest Ecology and Management, 2025)

A Natural Experiment to Evaluate Changes in Kids’ Meal Beverages in Fast-Food Restaurants Following a Healthy Default Policy, 2019-2022 - Angie L. Cradock; Jessica L. Barrett; Jason P. Block; Amy A. Bolton; Carolyn Bresnahan; Lisa Harnack; Stephanie McCulloch; Christina A. Roberto; Kristine Wiant; Alyssa Moran (Journal of the Academy of Nutrition and Dietetics, 2025)

Evaluating contaminated land and the environmental impact of oil spills in the Niger Delta region: a remote sensing-based approach - Seyi Adewale Adebangbe; Deborah P. Dixon; Brian Barrett (Environmental Monitoring and Assessment, 2025)
The Niger Delta region of Nigeria is a major oil-producing area which experiences frequent oil spills that severely impacts the local environment and communities. Effective environmental monitoring and management remain inadequate in this area due to negligence, slow response times following oil spills, and difficulties regarding access and safety. This study investigates the pervasive issue of oil spills in the Niger Delta region, by employing a remote sensing approach, leveraging geospatial cloud computing and machine learning to evaluate vegetation health indices (SR, SR2, NDVI, EVI2, GRNDVI, GNDVI) derived from PlanetScope satellite data. These indices were analysed using Slow Moving Average regression, which revealed significant declines in vegetation health following oil spill events. The contaminated landcovers exhibit a Spearman’s correlation coefficient (ρ) ranging from − 0.68 to − 0.82, P < 0.005 and P -values below 0.05 in most landcover categories, suggesting a clear and consistent downward trend in the indices’ values, reflecting a decrease in vegetation health in contaminated areas between 2016 and 2023. A random forest classifier further quantified the extent of contaminated land cover, demonstrating the effectiveness of this method for monitoring environmental damage in this challenging terrain. Contaminated vegetation, wetland, farmland, and grassland cover approximately 4% (1180 ha) of the total Niger Delta area. This integrated approach will enable decision-makers, including government agencies and oil companies, to gain a deeper understanding of the environmental consequences of oil pollution and implement targeted mitigation and remediation strategies.

Neurobehavioral effects of gestational exposure to mixtures of non-persistent endocrine disruptors in preschool-aged children: The environmental influences on child health outcomes (ECHO) program - Dorothy Nakiwala; John L. Adgate; Greta Wilkening; Emily S. Barrett; Akhgar Ghassabian; Douglas M. Ruden; Susan L. Schantz; Anne L. Dunlop; Patricia A. Brennan; John D. Meeker; Dana Dabelea; Anne P. Starling (Environmental Research, 2025)

An investigation of personality in the Creek Chub, Semotilus atromaculatus - Jacob P. Barrett; Mollie F. Cashner (Environmental Biology of Fishes, 2024)
Intraspecific variation in personality traits is increasingly recognized as an important driver of ecological processes, particularly within the context of species invasions. However, relatively few studies have investigated personality in native fauna with more localized dispersal patterns, and information regarding the existence of personality in stream fishes native to the southeastern US is particularly lacking. In this study, we investigated personality in a native and widespread minnow species, the Creek Chub ( Semotilus atromaculatus ). Because of its piscivorous diet, use of its nests by nest-associating minnows, and its role as a colonizer of intermittent streams, the Creek Chub is an appropriate species for investigating the broad importance of personality-dependent processes to stream communities. We identified personality traits by estimating the repeatability of sociability, boldness, exploration, and activity in two separate behavioral assays and interpreted correlations between traits as evidence of behavioral syndromes. We did not detect repeatability for measures of sociability, possibly due to predatory interactions within this species. However, boldness, exploration, and activity were significantly repeatable and positively correlated, pointing to the existence of a bold-exploratory-active syndrome in this species. Larger individuals tended to be less active, and, despite a relatively small sample size, we detected significant differences between source populations for measures of boldness. This is the first study to identify the existence of a behavioral syndrome in Creek Chub and points to the importance of considering the role of personality in ecological processes involving native fauna.

Past and future effects of climate on the metapopulation dynamics of a Northeast Atlantic seabird across two centuries - Jana W. E. Jeglinski; Holly I. Niven; Sarah Wanless; Robert T. Barrett; Mike P. Harris; Jochen Dierschke; Jason Matthiopoulos (Ecology Letters, 2024)
Forecasting population responses to rapidly changing marine ecosystems requires mechanistic models integrating complex demographic processes, fitted to long time series, across large spatial scales. We used a Bayesian metapopulation model fit to colony census data and climatic covariates spanning 1900–2100 for all Northeast Atlantic colonies of an exemplar seabird, the Northern gannet ( Morus bassanus ) to investigate metapopulation dynamics under two climate scenarios. Fecundity varied non‐linearly with near‐surface air temperature and recruitment was depressed by sea surface temperature. We predict regime changes in density dependence as marine carrying capacities become constrained with increasing SST. Sensitivity to climate change varied across space and time, disadvantaging southwestern colonies whilst benefitting northern ones. Such sensitivity is noteworthy for a species previously assumed robust to climate change. We provide a spatial overview of climate sensitivities across a metapopulation to help with evidence‐based conservation management and open the way for similar mechanistic explorations for other colonial species.

An enclosure quality ranking framework for terrestrial animals in captivity - Alison M. Flanagan; Bryce Masuda; Koa Grabar; Lisa P. Barrett; Ronald R. Swaisgood (Applied Animal Behaviour Science, 2024)

Coding genome of a novel potyvirus, hogweed virus Y (HogVY) - Daisy Furrokh; Sam McGreig; Ian P. Adams; Ben Barrett; Aimee Fowkes; Anna Skelton; Adrian Fox; Ines Vazquez-Iglesias (Journal of Plant Pathology, 2024)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Counter‐gradient variation in gene expression between fish populations facilitates colonization of low‐dissolved oxygen environments - Janay A. Fox; David A. G. A. Hunt; Andrew P. Hendry; Lauren J. Chapman; Rowan D. H. Barrett (Molecular Ecology, 2024)
The role of phenotypic plasticity during colonization remains unclear due to the shifting importance of plasticity across timescales. In the early stages of colonization, plasticity can facilitate persistence in a novel environment; but over evolutionary time, processes such as genetic assimilation may reduce variation in plastic traits such that species with a longer evolutionary history in an environment can show lower levels of plasticity than recent invaders. Therefore, comparing species in the early stages of colonization to long‐established species provides a powerful approach for uncovering the role of phenotypic plasticity during different stages of colonization. We compared gene expression between low‐dissolved oxygen (DO) and high‐DO populations of two cyprinid fish: Enteromius apleurogramma , a species that has undergone a recent range expansion, and E. neumayeri , a long‐established native species in the same region. We sampled tissue either immediately after capture from the field or after a 2‐week acclimation under high‐DO conditions, allowing us to test for both evolved and plastic differences in low‐DO vs high‐DO populations of each species. We found that most genes showing candidate‐evolved differences in gene expression did not overlap with those showing plastic differences in gene expression. However, in the genes that did overlap, there was counter‐gradient variation such that plastic and evolved gene expression responses were in opposite directions in both species. Additionally, E. apleurogramma had higher levels of plasticity and evolved divergence in gene expression between field populations. We suggest that the higher level of plasticity and counter‐gradient variation may have allowed rapid genetic adaptation in E. apleurogramma and facilitated colonization. This study shows how counter‐gradient variation may impact the colonization of divergent oxygen environments.

Population parameters and conservation implications for one of the world's rarest marine fishes, the red handfish ( Thymichthys politus ) - Tyson J. Bessell; Rick D. Stuart‐Smith; Olivia J. Johnson; Neville S. Barrett; Tim P. Lynch; Andrew J. Trotter; Jemina Stuart‐Smith (Journal of Fish Biology, 2024)
Population estimates are required for effective conservation of many rare marine species, but can be difficult to obtain. The critically endangered red handfish ( Thymichthys politus ) is a coastal anglerfish known only from two fragmented populations in southeast Tasmania, Australia. It is at a high risk of extinction due to low numbers, loss of habitat, and the impacts of climate change. To aid conservation efforts, we provide the first empirical population size estimates of red handfish and investigate other important aspects of the species' life history, such as growth, habitat association, and movement. We surveyed both red handfish local populations via underwater visual census on scuba over 3 years and used photographic mark‐recapture techniques to estimate biological parameters. In 2020, the local adult population size was estimated to be 94 (95% confidence interval [CI] 40–231) adults at one site, and 7 (95% CI 5–10) at the other site, suggesting an estimated global population of 101 adults. Movement of individuals was extremely limited at 48.5 m (± 77.7 S.D. ) per year. We also found evidence of declining fish density, a declining proportion of juveniles, and increasing average fish size during the study. These results provide a serious warning that red handfish are likely sliding toward extinction, and highlight the urgent need to expand efforts for ex situ captive breeding to bolster numbers in the wild and maintain captive insurance populations, and to protect vital habitat to safeguard the species' ongoing survival in the wild.

How can cities achieve accelerated systemic decarbonization? Analysis of six frontrunner cities - Brendan F.D. Barrett; Gregory P. Trencher; Nhi Truong; Hiroshi Ohta (Sustainable Cities and Society, 2024)

Sediment-water fluxes of inorganic carbon and nutrients in the Pacific Arctic during the sea ice melt season - Lauren J. Barrett; Penny Vlahos; Douglas E. Hammond; Robert P. Mason (Continental Shelf Research, 2023)

Enhancing sea ice segmentation in Sentinel-1 images with atrous convolutions - Rafael Pires de Lima; Behzad Vahedi; Nick Hughes; Andrew P. Barrett; Walter Meier; Morteza Karimzadeh (International Journal of Remote Sensing, 2023)

Effects of Triclosan on the Development of Antimicrobial Resistance in the Environment: A Review - Chunzhen Wang; Shihai Liu; Haodi Feng; Holly Barrett; Hui Peng; S. H. P. Parakrama Karunaratne; Yu Zhang; Min Yang (Current Pollution Reports, 2023)

Increased levels of forestry best management practices reduce sediment delivery from Piedmont and Upper Coastal Plain clearcut harvests and access features, southeastern states, USA - Brent S. Hawks; M. Chad Bolding; W. Michael Aust; Scott M. Barrett; Erik B. Schilling; Stephen P. Prisley (Forest Ecology and Management, 2023)

A multicentre evaluation and expert recommendations of use of the newly developed BioFire Joint Infection polymerase chain reaction panel - Kordo Saeed; Nusreen Ahmad-Saeed; Rachel Annett; Gavin Barlow; Lucinda Barrett; Sara E. Boyd; Nicola Boran; Peter Davies; Harriet Hughes; Gwennan Jones; Laura Leach; Maureen Lynch; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Septic arthritis is a serious condition with significant morbidity and mortality, routinely diagnosed using culture. The FDA has recently approved the rapid molecular BioFire® Joint Infection Panel (BJIP) for synovial fluid. We aimed to evaluate the BJIP compared to culture and its potential use in patient management. A multicentre retrospective evaluation of BJIP was conducted in the UK and Ireland. Positive percent agreement (PPA) and negative percent agreement (NPA) were calculated between the BJIP and routine culture. A multidisciplinary team (MDT) discussion addressing the optimal or potential case use of the assay practice was facilitated. Three hundred ninety-nine surplus synovial fluid samples (~ 70% from native joints) from eight centres were processed using BJIP in addition to routine culture. An increased yield of positive results was detected using BJIP compared to routine culture (98 vs 83), giving an overall PPA of 91.6% and overall NPA of 93% for the BJIP compared to culture results. The BJIP detected resistant markers and additional organisms that could influence antibiotic choices including Neisseria gonorrhoeae and Kingella kingae . The MDT agreed that the assay could be used, in addition to standard methods, in adult and children patients with specialist advice use based on local needs. Rapid results from BJIP were assessed as having potential clinical impact on patient management. Organisms not included in the panel may be clinically significant and may limit the value of this test for PJI.

Patient–Specific Immersed Finite Element–Difference Model of Transcatheter Aortic Valve Replacement - Jordan A. Brown; Jae H. Lee; Margaret Anne Smith; David R. Wells; Aaron Barrett; Charles Puelz; John P. Vavalle; Boyce E. Griffith (Annals of Biomedical Engineering, 2023)
Transcatheter aortic valve replacement (TAVR) first received FDA approval for high-risk surgical patients in 2011 and has been approved for low-risk surgical patients since 2019. It is now the most common type of aortic valve replacement, and its use continues to accelerate. Computer modeling and simulation (CM&S) is a tool to aid in TAVR device design, regulatory approval, and indication in patient-specific care. This study introduces a computational fluid-structure interaction (FSI) model of TAVR with Medtronic’s CoreValve Evolut R device using the immersed finite element-difference (IFED) method. We perform dynamic simulations of crimping and deployment of the Evolut R, as well as device behavior across the cardiac cycle in a patient-specific aortic root anatomy reconstructed from computed tomography (CT) image data. These IFED simulations, which incorporate biomechanics models fit to experimental tensile test data, automatically capture the contact within the device and between the self-expanding stent and native anatomy. Further, we apply realistic driving and loading conditions based on clinical measurements of human ventricular and aortic pressures and flow rates to demonstrate that our Evolut R model supports a physiological diastolic pressure load and provides informative clinical performance predictions.

Characteristics of extreme daily precipitation events over the Canadian Arctic - Mark C. Serreze; Jessica Voveris; Andrew P. Barrett; Shari Fox; Peter D. Blanken; Alex Crawford (International Journal of Climatology, 2022)
Given growing interest in extreme high‐latitude weather events, we use records from nine meteorological stations and atmospheric reanalysis data to examine extreme daily precipitation events (leading, 99th and 95th percentile) over Arctic Canada. Leading events span 90 mm at Cape Dyer, along the southeast coast of Baffin Island, to 26 mm at Sachs Harbour, on the southwest coast of Banks Island. The 95th percentiles range from 20 to 30% of leading event sizes. Extreme events are most common on or near the month of climatological peak precipitation. Contrasting with Eurasian continental sites having a July precipitation peak corresponding to the seasonal peak in precipitable water, seasonal cycles in precipitation and the frequency of extremes over Arctic Canada are more varied, reflecting marine influences. At Cape Dyer and Clyde River, mean precipitation and the frequency of extremes peak in October when the atmosphere is quickly cooling, promoting strong evaporation from Baffin Bay. At all stations, leading events involved snowfall and strong winds and were associated with cyclone passages (mostly of relatively strong storms). They also involved strong vapour fluxes, sometimes associated with atmospheric rivers or their remnants. The most unusual sequence of events identified here occurred at Clyde River, where the three largest recorded precipitation events occurred in April of 1977. Obtaining first‐hand accounts of this series of events has proven elusive. Identified links between extreme events and atmospheric rivers demonstrates the need to better understand how the characteristics of such features will change in the future.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Correction to: Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Childhood blood lead levels and environmental risk factors in Madagascar - Wyatt M. Champion; Adaline M. Buerck; Christopher Nenninger; Korede Yusuf; Luke J. P. Barrett; Lova Rakotoarisoa; Rinah Rakotondrazaka; Katherine Alfredo; Jeffrey Cunningham; Mahmooda Khaliq; James R. Mihelcic (Environmental Science and Pollution Research, 2022)

Mapping risk to plant populations from short fire intervals via relationships between maturation period and environmental productivity - Carl R. Gosper; Ben P. Miller; Rachael V. Gallagher; Janine Kinloch; Richard van Dongen; Emma Adams; Sarah Barrett; Anne Cochrane; Sarah Comer; Lachlan McCaw; Russell G. Miller; Suzanne M. Prober; et al. (Plant Ecology, 2022)

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

High throughput sequencing of a 42 year-old isolate of hogweed virus 4 (HV4) reveals that is a member of the genus Chordovirus - Adrian Fox; Aimee Fowkes; Ines Vazquez-Iglesias; Christine Conyers; Ben Barrett; Sam McGreig; Ian P. Adams (Journal of Plant Pathology, 2022)

Understanding the stimulus effects of nicotine and bupropion in a drug-drug discriminated goal-tracking task - Andrea E. Moran; Y. Wendy Huynh; Andrew P. Finkner; Carly Selleck; Aelyn Thompson; Scott T. Barrett; Rick A. Bevins (Psychopharmacology, 2022)

Evaluating cannabidiol (CBD) expectancy effects on acute stress and anxiety in healthy adults: a randomized crossover study - Toni C. Spinella; Sherry H. Stewart; Julia Naugler; Igor Yakovenko; Sean P. Barrett (Psychopharmacology, 2021)
Rationale Cannabidiol (CBD) has been reported to attenuate stress and anxiety, but little is known about the extent to which such effects result from pharmacological versus expectancy factors. Objectives We evaluated whether CBD expectancy alone could influence stress, anxiety, and mood, and the extent to which beliefs regarding CBD effects predicted these responses. Methods In this randomized crossover study, 43 health adults (23 women) attended two experimental laboratory sessions, where they self-administered CBD-free hempseed oil sublingually. During one session, they were (incorrectly) informed that the oil contained CBD and in the other session, that the oil was CBD-free. Following administration, participants engaged in the Maastricht Acute Stress Test (MAST). Heart rate variability (HRV) was assessed continuously, and subjective state was assessed at baseline, 90-min following oil administration, immediately following the MAST, and after a 10-min recovery period. Results The CBD expectancy condition was associated with increased sedation as well as with changes in HRV that were consistent with heightened anticipatory stress regulation. Overall, there were no systematic changes in subjective stress, or anxiety, according to expectancy condition. However, participants who endorsed strong a priori beliefs that CBD has anxiolytic properties reported significantly diminished anxiety in the CBD expectancy condition. Conclusions CBD expectancy alone impacted several subjective and physiological responses. Additionally, expectancy-related factors were implicated in anxiolytic effects of CBD for those who believed it was helpful for such purposes, emphasizing the need to measure and control for CBD-related expectancies in clinical research that involves the administration of CBD.

VLBI measurement of the vector baseline between geodetic antennas at Kokee Park Geophysical Observatory, Hawaii - A. E. Niell; J. P. Barrett; R. J. Cappallo; B. E. Corey; P. Elosegui; D. Mondal; G. Rajagopalan; C. A. Ruszczyk; M. A. Titus (Journal of Geodesy, 2021)
We measured the components of the 31-m-long vector between the two very-long-baseline interferometry (VLBI) antennas at the Kokee Park Geophysical Observatory (KPGO), Hawaii, with approximately 1 mm precision using phase delay observables from dedicated VLBI observations in 2016 and 2018. The two KPGO antennas are the 20 m legacy VLBI antenna and the 12 m VLBI Global Observing System (VGOS) antenna. Independent estimates of the vector between the two antennas were obtained by the National Geodetic Survey (NGS) using standard optical surveys in 2015 and 2018. The uncertainties of the latter survey were 0.3 and 0.7 mm in the horizontal and vertical components of the baseline, respectively. We applied corrections to the measured positions for the varying thermal deformation of the antennas on the different days of the VLBI and survey measurements, which can amount to 1 mm, bringing all results to a common reference temperature. The difference between the VLBI and survey results are 0.2 ± 0.4 mm, −1.3 ± 0.4 mm, and 0.8 ± 0.8 mm in the East, North, and Up topocentric components, respectively. We also estimate that the Up component of the baseline may suffer from systematic errors due to gravitational deformation and uncalibrated instrumental delay variations at the 20 m antenna that may reach ± 10 and −2 mm, respectively, resulting in an accuracy uncertainty on the order of 10 mm for the relative heights of the antennas. Furthermore, possible tilting of the 12 m antenna increases the uncertainties in the differences in the horizontal components to 1.0 mm. These results bring into focus the importance of (1) correcting to a common reference temperature the measurements of the reference points of all geodetic instruments within a site, (2) obtaining measurements of the gravitational deformation of all antennas, and (3) monitoring local motions of the geodetic instruments. These results have significant implications for the accuracy of global reference frames that require accurate local ties between geodetic instruments, such as the International Terrestrial Reference Frame (ITRF).

Using seasonal genomic changes to understand historical adaptation to new environments: Parallel selection on stickleback in highly‐variable estuaries - Alan Garcia‐Elfring; Antoine Paccard; Timothy J. Thurman; Ben A. Wasserman; Eric P. Palkovacs; Andrew P. Hendry; Rowan D. H. Barrett (Molecular Ecology, 2021)
Parallel evolution is considered strong evidence for natural selection. However, few studies have investigated the process of parallel selection as it plays out in real time. The common approach is to study historical signatures of selection in populations already well adapted to different environments. Here, to document selection under natural conditions, we study six populations of threespine stickleback ( Gasterosteus aculeatus ) inhabiting bar‐built estuaries that undergo seasonal cycles of environmental changes. Estuaries are periodically isolated from the ocean due to sandbar formation during dry summer months, with concurrent environmental shifts that resemble the long‐term changes associated with postglacial colonization of freshwater habitats by marine populations. We used pooled whole‐genome sequencing to track seasonal allele frequency changes in six of these populations and search for signatures of natural selection. We found consistent changes in allele frequency across estuaries, suggesting a potential role for parallel selection. Functional enrichment among candidate genes included transmembrane ion transport and calcium binding, which are important for osmoregulation and ion balance. The genomic changes that occur in threespine stickleback from bar‐built estuaries could provide a glimpse into the early stages of adaptation that have occurred in many historical marine to freshwater transitions.

Does getting defensive get you anywhere?—Seasonal balancing selection, temperature, and parasitoids shape real‐world, protective endosymbiont dynamics in the pea aphid - Andrew H. Smith; Michael P. O’Connor; Brooke Deal; Coleman Kotzer; Amanda Lee; Barrett Wagner; Jonah Joffe; Stephen Woloszynek; Kerry M. Oliver; Jacob A. Russell (Molecular Ecology, 2021)
Facultative, heritable endosymbionts are found at intermediate prevalence within most insect species, playing frequent roles in their hosts’ defence against environmental pressures. Focusing on Hamiltonella defensa , a common bacterial endosymbiont of aphids, we tested the hypothesis that such pressures impose seasonal balancing selection, shaping a widespread infection polymorphism. In our studied pea aphid ( Acyrthosiphon pisum ) population, Hamiltonella frequencies ranged from 23.2% to 68.1% across a six‐month longitudinal survey. Rapid spikes and declines were often consistent across fields, and we estimated that selection coefficients for Hamiltonella ‐infected aphids changed sign within this field season. Prior laboratory research suggested antiparasitoid defence as the major Hamiltonella benefit, and costs under parasitoid absence. While a prior field study suggested these forces can sometimes act as counter‐weights in a regime of seasonal balancing selection, our present survey showed no significant relationship between parasitoid wasps and Hamiltonella prevalence. Field cage experiments provided some explanation: parasitoids drove modest ~10% boosts to Hamiltonella frequencies that would be hard to detect under less controlled conditions. They also showed that Hamiltonella was not always costly under parasitoid exclusion, contradicting another prediction. Instead, our longitudinal survey – and two overwintering studies – showed temperature to be the strongest predictor of Hamiltonella prevalence. Matching some prior lab discoveries, this suggested that thermally sensitive costs and benefits, unrelated to parasitism, can shape Hamiltonella dynamics. These results add to a growing body of evidence for rapid, seasonal adaptation in multivoltine organisms, suggesting that such adaptation can be mediated through the diverse impacts of heritable bacterial endosymbionts.

Laboratory and clinical impacts of an overnight laboratory service - Paul R. Ingram; L. Barrett; E. Raby; P. Boan; G. A. Weaire-Buchanan; H. Darragh; P. Lloyd; I. Kay; J. Flexman (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Male characteristics as predictors of genital color and display variation in vervet monkeys - Mirjam M. I. Young; Sandra Winters; Christopher Young; Brigitte M. Weiß; Jolyon Troscianko; André Ganswindt; Louise Barrett; S. Peter Henzi; James P. Higham; Anja Widdig (Behavioral Ecology and Sociobiology, 2020)
In the animal kingdom, conspicuous colors are often used for inter- and intra-sexual communication. Even though primates are the most colorful mammalian taxon, many questions, including what potential information color signals communicate to social partners, are not fully understood. Vervet monkeys ( Chlorocebus pygerythrus ) are ideal to examine the covariates of color signals. Males have multi-colored genitals, which they present during distinctive male-male interactions, known as the “Red-White-and-Blue” (RWB) display, but the genitals are also visible across a variety of other contexts, and it is unclear what this color display signals to recipients. We recorded genital color presentations and standardized digital photos of male genitals ( N = 405 photos) over one mating season for 20 adult males in three groups at the Samara Private Game Reserve, South Africa. We combined these with data on male characteristics (dominance, age, tenure length, injuries, and fecal glucocorticoid metabolite concentrations). Using visual modeling methods, we measured single colors (red, white, blue) but also the contrasts between colors. We assessed the frequency of the RWB genital display and male variation in genital coloration and linked this to male characteristics. Our data suggest that the number of genital displays increased with male dominance. However, none of the variables investigated explained the inter- and intra-individual variation in male genital coloration. These results suggest that the frequency of the RWB genital display, but not its color value, is related to dominance, providing valuable insights on covariation in color signals and their display in primates. Significance statement Conspicuous colors in animals often communicate individual quality to mates and rivals. By investigating vervet monkeys, a primate species in which males present their colorful genitals within several behavioral displays, we aim to identify the covariates of such colorful signals and their behavioral display. Using visual modeling methods for the color analysis and combining behavioral display data and color data with male characteristics, we found that high-ranking males displayed their colorful genitals more frequently than lower-ranking ones. In contrast, color variation was not influenced by male dominance, age, tenure length, or health. Our results can serve as a basis for future investigations on the function of colorful signals and behavioral displays, such as a badge of status or mate choice in primates.

Prolonged exposure to manure from livestock‐administered antibiotics decreases ecosystem carbon‐use efficiency and alters nitrogen cycling - Carl Wepking; Brian Badgley; John E. Barrett; Katharine F. Knowlton; Jane M. Lucas; Kevan J. Minick; Partha P. Ray; Sarah E. Shawver; Michael S. Strickland (Ecology Letters, 2019)
Microbial communities drive soil ecosystem function but are also susceptible to environmental disturbances. We investigated whether exposure to manure sourced from cattle either administered or not administered antibiotics affected microbially mediated terrestrial ecosystem function. We quantified changes in microbial community composition via amplicon sequencing, and terrestrial elemental cycling via a stable isotope pulse‐chase. Exposure to manure from antibiotic‐treated cattle caused: (i) changes in microbial community structure; and (ii) alterations in elemental cycling throughout the terrestrial system. This exposure caused changes in fungal : bacterial ratios, as well as changes in bacterial community structure. Additionally, exposure to manure from cattle treated with pirlimycin resulted in an approximate two‐fold increase in ecosystem respiration of recently fixed‐carbon, and a greater proportion of recently added nitrogen in plant and soil pools compared to the control manure. Manure from antibiotic‐treated cattle therefore affects terrestrial ecosystem function via the soil microbiome, causing decreased ecosystem carbon use efficiency, and altered nitrogen cycling.

Runoff from glacier ice and seasonal snow in High Asia: separating melt water sources in river flow - Richard L. Armstrong; Karl Rittger; Mary J. Brodzik; Adina Racoviteanu; Andrew P. Barrett; Siri-Jodha Singh Khalsa; Bruce Raup; Alice F. Hill; Alia L. Khan; Alana M. Wilson; Rijan Bhakta Kayastha; Florence Fetterer; et al. (Regional Environmental Change, 2019)

Paternity analysis reveals constraints on hybridization potential between native and introduced bluebells (Hyacinthoides) - D. D. Kohn; M. Ruhsam; P. E. Hulme; S. C. H. Barrett; P. M. Hollingsworth (Conservation Genetics, 2019)

Contrasting arsenic cycling in strongly and weakly stratified contaminated lakes: Evidence for temperature control on sediment–water arsenic fluxes - P. M. Barrett; E. A. Hull; K. Burkart; O. Hargrave; J. McLean; V. F. Taylor; B. P. Jackson; J. E. Gawel; R. B. Neumann (Limnology and Oceanography, 2019)
Arsenic contamination of lakebed sediments is widespread due to a range of human activities, including herbicide application, waste disposal, mining, and smelter operations. The threat to aquatic ecosystems and human health is dependent on the degree of mobilization from sediments into overlying water columns and exposure of aquatic organisms. We undertook a mechanistic investigation of arsenic cycling in two impacted lakes within the Puget Sound region, a shallow weakly stratified lake and a deep seasonally stratified lake, with similar levels of lakebed arsenic contamination. We found that the processes that cycle arsenic between sediments and the water column differed greatly in shallow and deep lakes. In the shallow lake, seasonal temperature increases at the lakebed surface resulted in high porewater arsenic concentrations that drove larger diffusive fluxes of arsenic across the sediment–water interface compared to the deep, stratified lake where the lakebed remained ~10°C cooler. Plankton in the shallow lake accumulated up to an order of magnitude more arsenic than plankton in the deep lake due to elevated aqueous arsenic concentrations in oxygenated waters and low phosphate : arsenate ratios in the shallow lake. As a result, strong arsenic mobilization from sediments in the shallow lake was countered by large arsenic sedimentation rates out of the water column driven by plankton settling.

Predictive ability of genomic selection models in a multi-population perennial ryegrass training set using genotyping-by-sequencing - Marty J. Faville; Siva Ganesh; Mingshu Cao; M. Z. Zulfi Jahufer; Timothy P. Bilton; H. Sydney Easton; Douglas L. Ryan; Jason A. K. Trethewey; M. Philip Rolston; Andrew G. Griffiths; Roger Moraga; Casey Flay; et al. (Theoretical and Applied Genetics, 2018)

Advancing Coastal Habitat Resiliency Through Landscape-Scale Assessment - Georgia Basso; Jamie M. P. Vaudrey; Kevin O'Brien; Juliana Barrett (Coastal Management, 2018)

CHIPS: an Extensible Toolbox for Cellular and Hemodynamic Two-Photon Image Analysis - Matthew J. P. Barrett; Kim David Ferrari; Jillian L. Stobart; Martin Holub; Bruno Weber (Neuroinformatics, 2018)

Methylene blue modulates functional connectivity in the human brain - Pavel Rodriguez; Amar P. Singh; Kristen E. Malloy; Wei Zhou; Douglas W. Barrett; Crystal G. Franklin; Wilson B. Altmeyer; Juan E. Gutierrez; Jinqi Li; Betty L. Heyl; Jack L. Lancaster; F. Gonzalez-Lima; et al. (Brain Imaging and Behavior, 2017)

Multilocus approaches for the measurement of selection on correlated genetic loci - Zachariah Gompert; Scott P. Egan; Rowan D. H. Barrett; Jeffrey L. Feder; Patrik Nosil (Molecular Ecology, 2017)
The study of ecological speciation is inherently linked to the study of selection. Methods for estimating phenotypic selection within a generation based on associations between trait values and fitness (e.g. survival) of individuals are established. These methods attempt to disentangle selection acting directly on a trait from indirect selection caused by correlations with other traits via multivariate statistical approaches (i.e. inference of selection gradients). The estimation of selection on genotypic or genomic variation could also benefit from disentangling direct and indirect selection on genetic loci. However, achieving this goal is difficult with genomic data because the number of potentially correlated genetic loci ( p ) is very large relative to the number of individuals sampled ( n ). In other words, the number of model parameters exceeds the number of observations ( p ≫ n ). We present simulations examining the utility of whole‐genome regression approaches (i.e. Bayesian sparse linear mixed models) for quantifying direct selection in cases where p ≫ n . Such models have been used for genome‐wide association mapping and are common in artificial breeding. Our results show they hold promise for studies of natural selection in the wild and thus of ecological speciation. But we also demonstrate important limitations to the approach and discuss study designs required for more robust inferences.

Coastal Vertebrate Exposure to Predicted Habitat Changes Due to Sea Level Rise - Elizabeth A. Hunter; Nathan P. Nibbelink; Clark R. Alexander; Kyle Barrett; Lara F. Mengak; Rachel K. Guy; Clinton T. Moore; Robert J. Cooper (Environmental Management, 2015)

Extreme daily precipitation events at Spitsbergen, an Arctic Island - Mark C. Serreze; Alex D. Crawford; Andrew P. Barrett (International Journal of Climatology, 2015)
Daily station records and output from the MERRA atmospheric reanalysis for the period 1979 onwards are used to examine extreme daily precipitation events at Ny Ålesund and three other sites located on Spitsbergen. Spitsbergen, lying between 77°N and 80°N, is the largest island of the Svalbard Archipelago. The region is frequently influenced by extratropical cyclones associated with the North Atlantic cyclone track and (in winter) regional baroclinicity due to proximity to the sea ice margin. Despite the stronger cyclone activity in winter, extreme precipitation events at Ny Ålesund, defined as those in the top 1% of the statistical distribution, can occur year round. On the basis of a composite analysis, extreme events tend to occur when the region is influenced by a trough of low sea level pressure extending from the southwest, southerly winds in the troposphere, positive anomalies in precipitable water, and pronounced upward motion (negative omega) at 500 hPa . This is linked to positive anomalies in 500 hPa heights over the Barents Sea and negative anomalies over Greenland. While individual extreme events do not share all of these characteristics, strong southerly flow and positive anomalies in precipitable water provide a near common thread. Reflecting local topography, extremes at Ny Ålesund are typically not well represented at other stations on the island, but there are notable exceptions. Some of the largest precipitation events can be associated with features resembling ‘atmospheric rivers’, seen as narrow corridors of pronounced positive anomalies in precipitable water extending thousands of kilometres south into the subtropical Atlantic. There is no systematic pattern of temporal trends in the frequency or magnitude of extremes.

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

Anterior–posterior dissociation of the default mode network in dogs - Sreenath P. Kyathanahally; Hao Jia; Oleg M. Pustovyy; Paul Waggoner; Ronald Beyers; John Schumacher; Jay Barrett; Edward E. Morrison; Nouha Salibi; Thomas S. Denney; Vitaly J. Vodyanoy; Gopikrishna Deshpande (Brain Structure and Function, 2015)

Strategic Rat Control for Restoring Populations of Native Species in Forest Fragments - DOUG P. ARMSTRONG; NIC GORMAN; RHONDA PIKE; BRIGITTE KREIGENHOFER; NIKKI MCARTHUR; SUSANNE GOVELLA; PAUL BARRETT; YVAN RICHARD (Conservation Biology, 2014)
Forest fragments have biodiversity value that may be enhanced through management such as control of non‐native predators. However, such efforts may be ineffective, and research is needed to ensure that predator control is done strategically. We used Bayesian hierarchical modeling to estimate fragment‐specific effects of experimental rat control on a native species targeted for recovery in a New Zealand pastoral landscape. The experiment was a modified BACI (before‐after‐control‐impact) design conducted over 6 years in 19 forest fragments with low‐density subpopulations of North Island Robins (Petroica longipes). The aim was to identify individual fragments that not only showed clear benefits of rat control, but also would have a high probability of subpopulation growth even if they were the only fragment managed. We collected data on fecundity, adult and juvenile survival, and juvenile emigration, and modeled the data in an integrated framework to estimate the expected annual growth rate (λ) of each subpopulation with and without rat control. Without emigration, subpopulation growth was estimated as marginal (λ = 0.95–1.05) or negative (λ = 0.74–0.90) without rat control, but it was estimated as positive in all fragments (λ = 1.4–2.1) if rats were controlled. This reflected a 150% average increase in fecundity and 45% average increase in adult female survival. The probability of a juvenile remaining in its natal fragment was 0.37 on average, but varied with fragment connectivity. With juvenile emigration added, 6 fragments were estimated to have a high (>0.8) probability of being self‐sustaining (λ > 1) with rat control. The key factors affecting subpopulation growth rates under rat control were low connectivity and stock fencing because these factors were associated with lower juvenile emigration and higher fecundity, respectively. However, there was also substantial random variation in adult survival among fragments, illustrating the importance of hierarchical modeling for fragmentation studies. Control Estratégico de Ratas para Restaurar Poblaciones de Especies Nativas en Fragmentos de Bosque

The association between neighborhood socioeconomic status and ovarian cancer tumor characteristics - Caryn E. Peterson; Garth H. Rauscher; Timothy P. Johnson; Carolyn V. Kirschner; Richard E. Barrett; Seijeoung Kim; Marian L. Fitzgibbon; Charlotte E. Joslin; Faith G. Davis (Cancer Causes & Control, 2014)

Implications of Macroalgal Isolation by Distance for Networks of Marine Protected Areas - HALLEY M. S. DURRANT; CHRISTOPHER P. BURRIDGE; BRENDAN P. KELAHER; NEVILLE S. BARRETT; GRAHAM J. EDGAR; MELINDA A. COLEMAN (Conservation Biology, 2014)
The global extent of macroalgal forests is declining, greatly affecting marine biodiversity at broad scales through the effects macroalgae have on ecosystem processes, habitat provision, and food web support. Networks of marine protected areas comprise one potential tool that may safeguard gene flow among macroalgal populations in the face of increasing population fragmentation caused by pollution, habitat modification, climate change, algal harvesting, trophic cascades, and other anthropogenic stressors. Optimal design of protected area networks requires knowledge of effective dispersal distances for a range of macroalgae. We conducted a global meta‐analysis based on data in the published literature to determine the generality of relation between genetic differentiation and geographic distance among macroalgal populations. We also examined whether spatial genetic variation differed significantly with respect to higher taxon, life history, and habitat characteristics. We found clear evidence of population isolation by distance across a multitude of macroalgal species. Genetic and geographic distance were positively correlated across 49 studies; a modal distance of 50–100 km maintained F ST Implicaciones del Aislamiento por Distancia de Macroalgas para Redes de Áreas Marinas Protegidas

Conservation of the Critically Endangered Eastern Australian Population of the Grey Nurse Shark (Carcharias taurus) Through Cross-Jurisdictional Management of a Network of Marine-Protected Areas - Tim P. Lynch; Robert Harcourt; Graham Edgar; Neville Barrett (Environmental Management, 2013)

Skeletal muscle satellite cell migration to injured tissue measured with111In-oxine and high-resolution SPECT imaging - Jennifer L. Elster; Christopher R. Rathbone; Zhonglin Liu; Xiasong Liu; Harrison H. Barrett; Robert P. Rhoads; Ronald E. Allen (Journal of Muscle Research and Cell Motility, 2013)

Detecting changes in surface soil moisture content using differential SAR interferometry - B. Barrett; P. Whelan; E. Dwyer (International Journal of Remote Sensing, 2013)

Strategic Biomarkers for Drug Development in Treating Rare Diseases and Diseases in Neonates and Infants - Jane P. F. Bai; Jeffrey S. Barrett; Gibert J. Burckart; Bernd Meibohm; Hari Cheryl Sachs; Lynne Yao (The AAPS Journal, 2013)

Chemosensory responses of juvenile Coho salmon, Oncorhynchus kisutch, Dolly Varden, Salvelinus malma, and sculpins (Cottus spp.) to eggs and other tissues from adult Pacific salmon - Thomas P. Quinn; Andrew H. Dittman; Hannah Barrett; Curry Cunningham; Morgan H. Bond (Environmental Biology of Fishes, 2012)

Evidence for scent marking in vervet monkeys? - N. J. Freeman; G. M. Pasternak; T. L. Rubi; L. Barrett; S. P. Henzi (Primates, 2012)

The effects of acute doses of nicotine on video lottery terminal gambling in daily smokers - Daniel S. McGrath; Sean P. Barrett; Sherry H. Stewart; Evan A. Schmid (Psychopharmacology, 2012)

The Arctic’s rapidly shrinking sea ice cover: a research synthesis - Julienne C. Stroeve; Mark C. Serreze; Marika M. Holland; Jennifer E. Kay; James Malanik; Andrew P. Barrett (Climatic Change, 2012)

A c‐type cytochrome and a transcriptional regulator responsible for enhanced extracellular electron transfer in Geobacter sulfurreducens revealed by adaptive evolution - Pier‐Luc Tremblay; Zarath M. Summers; Richard H. Glaven; Kelly P. Nevin; Karsten Zengler; Christian L. Barrett; Yu Qiu; Bernhard O. Palsson; Derek R. Lovley (Environmental Microbiology, 2011)
Summary The stimulation of subsurface microbial metabolism often associated with engineered bioremediation of groundwater contaminants presents subsurface microorganisms, which are adapted for slow growth and metabolism in the subsurface, with new selective pressures. In order to better understand how Geobacter species might adapt to selective pressure for faster metal reduction in the subsurface, Geobacter sulfurreducens was put under selective pressure for rapid Fe(III) oxide reduction. The genomes of two resultant strains with rates of Fe(III) oxide reduction that were 10‐fold higher than those of the parent strain were resequenced. Both strains contain either a single base‐pair change or a 1 nucleotide insertion in a GEMM riboswitch upstream of GSU1761, a gene coding for the periplasmic c ‐type cytochrome designated PgcA. GSU1771, a gene coding for a SARP regulator, was also mutated in both strains. Introduction of either of the GEMM riboswitch mutations upstream of pgcA in the wild‐type increased the abundance of pgcA transcripts, consistent with increased expression of pgcA in the adapted strains. One of the mutations doubled the rate of Fe(III) oxide reduction. Interruption of GSU1771 doubled the Fe(III) oxide reduction rate. This was associated with an increased in expression of pilA , the gene encoding the structural protein for the pili thought to function as microbial nanowires. The combination of the GSU1771 interruption with either of the pgcA mutations resulted in a strain that reduced Fe(III) as fast as the comparable adapted strain. These results suggest that the accumulation of a small number of beneficial mutations under selective pressure, similar to that potentially present during bioremediation, can greatly enhance the capacity for Fe(III) oxide reduction in G. sulfurreducens . Furthermore, the results emphasize the importance of the c‐type cytochrome PgcA and pili in Fe(III) oxide reduction and demonstrate how adaptive evolution studies can aid in the elucidation of complex mechanisms, such as extracellular electron transfer.

The complete genome sequence of Canna yellow streak virus - W. A. Monger; I. P. Adams; R. H. Glover; B. Barrett (Archives of Virology, 2010)

Photographic mark-recapture analysis of clustered mammal-eating killer whales around the Aleutian Islands and Gulf of Alaska - J. Durban; D. Ellifrit; M. Dahlheim; J. Waite; C. Matkin; L. Barrett-Lennard; G. Ellis; R. Pitman; R. LeDuc; P. Wade (Marine Biology, 2010)

Cyclicity in the structure of female baboon social networks - S. P. Henzi; D. Lusseau; T. Weingrill; C. P. van Schaik; L. Barrett (Behavioral Ecology and Sociobiology, 2009)

Persistent effects of a discrete warming event on a polar desert ecosystem - J. E. BARRETT; R. A. VIRGINIA; D. H. WALL; P. T. DORAN; A. G. FOUNTAIN; K. A. WELCH; W. B. LYONS (Global Change Biology, 2008)
A discrete warming event (December 21, 2001–January 12, 2002) in the McMurdo Dry Valleys, Antarctica, enhanced glacier melt, stream flow, and melting of permafrost. Effects of this warming included a rapid rise in lake levels and widespread increases in soil water availability resulting from melting of subsurface ice. These increases in liquid water offset hydrologic responses to a cooling trend experienced over the previous decade and altered ecosystem properties in both aquatic and terrestrial ecosystems. Here, we present hydrological and meteorological data from the McMurdo Dry Valleys Long Term Ecological Research project to examine the influence of a discrete climate event (warming of >2 °C) on terrestrial environments and soil biotic communities. Increases in soil moisture following this event stimulated populations of a subordinate soil invertebrate species ( Eudorylaimus antarcticus , Nematoda). The pulse of melt‐water had significant influences on Taylor Valley ecosystems that persisted for several years, and illustrates that the importance of discrete climate events, long recognized in hot deserts, are also significant drivers of soil and aquatic ecosystems in polar deserts. Thus, predictions of Antarctic ecosystem responses to climate change which focus on linear temperature trends may miss the potentially significant influence of infrequent climate events on hydrology and linked ecological processes.

The Future of Scattered Trees in Agricultural Landscapes - P. GIBBONS; D. B. LINDENMAYER; J. FISCHER; A. D. MANNING; A. WEINBERG; J. SEDDON; P. RYAN; G. BARRETT (Conservation Biology, 2008)
Mature trees scattered throughout agricultural landscapes are critical habitat for some biota and provide a range of ecosystem services. These trees are declining in intensively managed agricultural landscapes globally. We developed a simulation model to predict the rates at which these trees are declining, identified the key variables that can be manipulated to mitigate this decline, and compared alternative management proposals. We used the initial numbers of trees in the stand, the predicted ages of these trees, their rate of growth, the number of recruits established, the frequency of recruitment, and the rate of tree mortality to simulate the dynamics of scattered trees in agricultural landscapes. We applied this simulation model to case studies from Spain, United States, Australia, and Costa Rica. We predicted that mature trees would be lost from these landscapes in 90–180 years under current management. Existing management recommendations for these landscapes—which focus on increasing recruitment—would not reverse this trend. The loss of scattered mature trees was most sensitive to tree mortality, stand age, number of recruits, and frequency of recruitment. We predicted that perpetuating mature trees in agricultural landscapes at or above existing densities requires a strategy that keeps mortality among established trees below around 0.5% per year, recruits new trees at a rate that is higher than the number of existing trees, and recruits new trees at a frequency in years equivalent to around 15% of the maximum life expectancy of trees. Numbers of mature trees in landscapes represented by the case studies will decline before they increase, even if strategies of this type are implemented immediately. This decline will be greater if a management response is delayed.

Genetic evidence for the persistence of the critically endangered Sierra Nevada red fox in California - John D. Perrine; John P. Pollinger; Benjamin N. Sacks; Reginald H. Barrett; Robert K. Wayne (Conservation Genetics, 2007)

Model–data synthesis in terrestrial carbon observation: methods, data requirements and data uncertainty specifications - M. R. Raupach; P. J. Rayner; D. J. Barrett; R. S. DeFries; M. Heimann; D. S. Ojima; S. Quegan; C. C. Schmullius (Global Change Biology, 2005)
Systematic, operational, long‐term observations of the terrestrial carbon cycle (including its interactions with water, energy and nutrient cycles and ecosystem dynamics) are important for the prediction and management of climate, water resources, food resources, biodiversity and desertification. To contribute to these goals, a terrestrial carbon observing system requires the synthesis of several kinds of observation into terrestrial biosphere models encompassing the coupled cycles of carbon, water, energy and nutrients. Relevant observations include atmospheric composition (concentrations of CO 2 and other gases); remote sensing; flux and process measurements from intensive study sites; in situ vegetation and soil monitoring; weather, climate and hydrological data; and contemporary and historical data on land use, land use change and disturbance (grazing, harvest, clearing, fire). A review of model–data synthesis tools for terrestrial carbon observation identifies ‘nonsequential’ and ‘sequential’ approaches as major categories, differing according to whether data are treated all at once or sequentially. The structure underlying both approaches is reviewed, highlighting several basic commonalities in formalism and data requirements. An essential commonality is that for all model–data synthesis problems, both nonsequential and sequential, data uncertainties are as important as data values themselves and have a comparable role in determining the outcome. Given the importance of data uncertainties, there is an urgent need for soundly based uncertainty characterizations for the main kinds of data used in terrestrial carbon observation. The first requirement is a specification of the main properties of the error covariance matrix. As a step towards this goal, semi‐quantitative estimates are made of the main properties of the error covariance matrix for four kinds of data essential for terrestrial carbon observation: remote sensing of land surface properties, atmospheric composition measurements, direct flux measurements, and measurements of carbon stores.

Markers of experimental acute inflammation in the Wistar Han rat with particular reference to haptoglobin and C-reactive protein - P. S. Giffen; J. Turton; C. M. Andrews; P. Barrett; C. J. Clarke; K.-W. Fung; M. R. Munday; I. F. Roman; R. Smyth; K. Walshe; M. J. York (Archives of Toxicology, 2003)

Foot force direction in an isometric pushing task: prediction by kinematic and musculoskeletal models - M. W. Schmidt; C. López-Ortiz; P. S. Barrett; L. M. Rogers; K. G. Gruben (Experimental Brain Research, 2003)

Day length, latitude and behavioural (in)flexibility in baboons (Papio cynocephalus ursinus) - R. A. Hill; L. Barrett; D. Gaynor; T. Weingrill; P. Dixon; H. Payne; S. P. Henzi (Behavioral Ecology and Sociobiology, 2003)

Baculovirus expression and antigenic characterization of the capsid proteins of three Norwalk-like viruses - X. Jiang; W. M. Zhong; T. Farkas; P. W. Huang; N. Wilton; E. Barrett; D. Fulton; R. Morrow; D. O. Matson (Archives of Virology, 2002)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Effects of supplemental α-tocopherol and β-carotene on colorectal cancer: results from a controlled trial (Finland) - Demetrius Albanes; Nea Malila; Philip R. Taylor; Jussi K. Huttunen; Jarmo Virtamo; Brenda K. Edwards; Matti Rautalahti; Anne M. Hartman; Michael J. Barrett; Pirjo Pietinen; Terryl J. Hartman; Pentti Sipponen; et al. (Cancer Causes & Control, 2000)

Fate of dichlobenil in the River Ivel. 1: Determination of the residues of dichlobenil in sediment and water - P. R. F. Barrett; R. J. Makepeace (Hydrobiologia, 1999)

Long-term algal control in a reservoir using barley straw - P. R. F. Barrett; J. W. Littlejohn; J. Curnow (Hydrobiologia, 1999)

The distribution of macroinvertebrates and fishes in Tasmanian estuaries - G. J. Edgar; N. S. Barrett; P. R. Last (Journal of Biogeography, 1999)
The distributions of 390 taxa of benthic macroinvertebrates collected in forty‐eight estuaries and 101 fish species collected in seventy‐five Tasmanian estuaries were related to geographical and environmental variables. Distribution patterns for the two taxonomic groups were largely congruent at both between and within‐estuary scales. Faunal composition and the number of species collected at a site were primarily related to site salinity, the biomass of seagrass and tidal range. At the broader estuary scale, the distributions of macroinvertebrate and fish assemblages were primarily correlated with the presence of an entrance bar. Species richness varied with geographical location for both macrofauna and fishes, with highest numbers of species occurring in the Furneaux Group, north‐eastern Tasmania and south‐eastern Tasmania. These patterns primarily reflected differences in estuary type between regions rather than concentrations of locally endemic species. Although the majority of species collected during the study were marine vagrants, they constituted a very low proportion of total animal densities within estuaries. Only four species considered exotic to Tasmania were identifed. Nearly all species recorded from Tasmanian estuaries occurred widely within the state and have also been recorded in south‐eastern Australia. Only 1% of estuarine fish species and The low number of species recorded from estuaries along the western Tasmanian coast reflected extremely low faunal biomass in that area. This depression in biomass on the west coast was attributed to unusually low concentrations of dissolved nutrients in rivers and dark tannin‐stained waters which greatly restricted algal photosynthesis and primary production.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Scale-up of Adhesive Transdermal Drug Delivery Systems - Glenn A. Van Buskirk; Mario A. González; Vinod P. Shah; Scott Barnhardt; Colin Barrett; Stephen Berge; Gary Cleary; Keith Chan; Gordon Flynn; Thomas Foster; Robert Gale; Raymond Garrison; et al. (Pharmaceutical Research, 1997)